1999
DOI: 10.1038/sj.bjp.0702379
|View full text |Cite
|
Sign up to set email alerts
|

G‐protein activation by putative antagonists at mutant Thr373Lys α2A adrenergic receptors

Abstract: 1 Replacement of a threonine by a lysine at position 373 in the C-terminal portion of the third intracellular loop of the human a 2A -adrenergic receptor (a 2A AR) has been reported to generate a constitutively active mutant receptor in analogy with similar mutations in the a 1B and b 2 AR (Ren et al., 1993). In the present study, the mutant Thr 373 Lys a 2A AR receptor was investigated by measuring the formation of inositol phosphates in either the absence or presence of mouse G a15 protein in Cos-7 cells. 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 31 publications
6
37
0
Order By: Relevance
“…Combining expression of human a 2A -receptors (particularly with a mutation at Thr 373 ) with rat G á0 protein gives rise to a constitutively active receptor that tonically suppresses production of cyclic AMP (87,113,116). Under these rather artificial circumstances, RX 821002, in common with yohimbine/rauwolscine, usually behaves as an inverse agonist at á 2A -adrenoceptors (87,113).…”
Section: Rx 821002 As An Inverse Agonist At á 2 -Adrenoceptorsmentioning
confidence: 99%
“…Combining expression of human a 2A -receptors (particularly with a mutation at Thr 373 ) with rat G á0 protein gives rise to a constitutively active receptor that tonically suppresses production of cyclic AMP (87,113,116). Under these rather artificial circumstances, RX 821002, in common with yohimbine/rauwolscine, usually behaves as an inverse agonist at á 2A -adrenoceptors (87,113).…”
Section: Rx 821002 As An Inverse Agonist At á 2 -Adrenoceptorsmentioning
confidence: 99%
“…Earlier studies had reported little or no difference in antagonist binding for the CAM versus WT receptor (Ren et al, 1993;Wurch et al, 1999). Since yohimbine had previously been shown to be an inverse agonist for G i activation (Tian et al, 1994), we carefully determined its K d value for WT and CAM receptor-expressing membranes to see if the change in receptor conformation expected with the activating mutation would alter the [ 3 H]yohimbine binding.…”
Section: Radiochemicalsmentioning
confidence: 99%
“…The identification of ␣ 2A adrenergic inverse agonists and neutral antagonists that are more selective than yohimbine would be desirable. Furthermore, recent literature is contradictory as to whether the classical ␣ 2 -AR antagonists are inverse agonists or neutral antagonists (Tian et al, 1994;Wurch et al, 1999).…”
mentioning
confidence: 99%
“…In the ␤-adrenergic (40) and 5HT2A (41) Mutations in a number of GPCRs have been described that confer agonism to antagonists. Mutations in TM3 of the AT1 angiotensin receptor (39,42), rhodopsin (43), and the ␤-adrenergic receptor (40), in TM4 of -and ␦-opioid receptors (44), in TM6 of the -opioid receptor (45), in IC3 of the ␣ 2A -adrenergic receptor (46), and in IC2 of the V2 vasopressin receptor (47) conferred agonistic activity to antagonist ligands. The present study is the first description of a mutation in an extracellular domain that confers agonism to an antagonist.…”
Section: Chicken Gnrh Receptor Ec2 Confers Agonism To Antagonistsmentioning
confidence: 99%